RETRACTED: Inhibition of Bcl2L12 Attenuates Eosinophilia-Related Inflammation in the Heart - Chen, Xiao; Zhao, Mei-Zhen; Miao, Bei-Ping; Liu, Zhi-Qiang; Yang, Gui; Liu, Jiang-Qi; Yang, Ping-Chang; Song, Jiang-Ping (Frontiers in Immunology, 2020)
Eosinophilic inflammation plays a critical role in myocarditis (Mcd). The underlying mechanism remains to be further investigated. This study aims to investigate the effects of Bcl2 like protein 12 (Bcl2L12) on inducing defects of apoptosis in eosinophils (Eo) in the heart tissues. In this study, human explant hearts were collected. Eosinophilia and myocarditis (Mcd)-like inflammation were induced in the mouse heart by immunizing with murine cardiac α-myosin heavy chain (MyHCα) peptides. We observed that much more Eos were observed in heart tissues from patients with Mcd than those from patients with dilated cardiomyopathy (Dcm). Eos isolated from Mcd hearts showed the signs of apoptosis defects. Eo counts in the Mcd heart tissues was positively correlated with the Bcl2L12 expression in Eos of the heart tissues. Exposure to IL-5 in the culture induced the expression of Bcl2L12 in Eos. Bcl2L12 bound c-Myc, the transcription factor of FasL, to prevent c-Myc from binding to the FasL promoter, to restrict the FasL gene transcription in Eos. Inhibition of Bcl2L12 prevented the induction of eosinophilia and Mcd-like inflammation in the mouse heart. In conclusion, the Bcl2L12 expression contributes to apoptosis defects in Eos of the Mcd heart. Blocking Bcl2L12 prevents the eosinophilia induction and alleviates Mcd-like inflammation in mice.